Engineering Saccharomyces cerevisiae for Succinic Acid Production From Glycerol and Carbon Dioxide - Xiberras, Joeline; Klein, Mathias; de Hulster, Erik; Mans, Robert; Nevoigt, Elke (Frontiers in Bioengineering and Biotechnology, 2020)
Previously, our lab replaced the endogenous FAD-dependent pathway for glycerol catabolism in S. cerevisiae by the synthetic NAD-dependent dihydroxyacetone (DHA) pathway. The respective modifications allow the full exploitation of glycerol’s higher reducing power (compared to sugars) for the production of the platform chemical succinic acid (SA) via a reductive, carbon dioxide fixing and redox-neutral pathway in a production host robust for organic acid production. Expression cassettes for three enzymes converting oxaloacetate to SA in the cytosol (´SA module´) were integrated into the genome of UBR2CBS-DHA, an optimized CEN.PK derivative. Together with the additional expression of the heterologous dicarboxylic acid transporter DCT-02 from Aspergillus niger, a maximum SA titre of 10.7 g/L and a yield of 0.22 ± 0.01 g/g glycerol was achieved in shake flask (batch) cultures. Characterization of the constructed strain under controlled conditions in a bioreactor supplying additional carbon dioxide revealed that the carbon balance was closed to 96 %. Interestingly, the results of the current study indicate that the artificial ´SA module´ and endogenous pathways contribute to the SA production in a highly synergistic manner.